HUBUNGAN ANTARA LONELINESS DAN INTERAKSI PARASOSIAL PADA PENGGEMAR K-DRAMA - Maulidina Nabila Putri; Debora Basaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The advancement of technology and the acceleration of global cultural flow have made K-Dramas increasingly accessible and widely consumed. As a result, some individuals particularly those experiencing loneliness turn to K-Drama viewing as an emotional escape. This study aims to examine the relationship between lonelinessand parasocial interaction among K-Drama fans using a quantitative method with a correlational design, involving 413 participants selected through purposive sampling. The instruments utilized were the De Jong Gierveld Loneliness Scale by Gierveld and Tilburg (2006), adapted into Indonesian by Ningrum, E. P. (2020), and the Parasocial Interaction Scale derived from the Celebrity Attitude Scale (CAS) by Maltby et al. (2002), adapted into Indonesian by Zhafira, N. I. (2021). Pearson correlation analysis indicated a positive and significant relationship between loneliness and parasocial interaction among K-Drama fans in Indonesia. These findings suggest that parasocial interaction may serve as a coping mechanism that helps alleviate feelings of loneliness; however, excessive engagement may pose risks, including emotional dependence and avoidance of real social relationships.